Keterampilan Menulis Resensi Bahasa Indonesia Menggunakan Metode Mind Mapping pada Mahasiswa Administrasi Bisnis di Politeknik LP3I Makassar - Husni Bt Salam; Basri Basri (Departement of Mathematics Education, 2024)
Reviewing a work is one of the learning activities that trains students' writing skills. However, not all students have the skills to do a good review. The purpose of this study is to improve students' novel review writing learning outcomes using the mind mapping learning method. This study is a classroom action research carried out in two research cycles. Each research cycle consists of four stages, namely planning, implementing actions, observation, evaluation, and reflection. The subjects involved in this study were 35 students. Data collection in the study was carried out using observation, interview, questionnaire, and test methods. The research instruments were observation sheets and student writing ability test sheets. The data obtained in this study were analyzed using qualitative descriptive analysis techniques using a percentage formula. The results obtained in this study indicate that in the pre-action, the average student obtained an average score of 9 out of a maximum score of 20 with a percentage of 44% for the book identity aspect, 51% for the authorship aspect, 44% for the excellence aspect and 44% for the book's weaknesses aspect. After being given the mind mapping method in cycle 1, there was an increase, namely obtaining an average value of 12 with a percentage of 61% for the book identity aspect, 74% for the authorship aspect, 63% for the book's strengths and 61% for the book's weaknesses. In cycle 2, the average value obtained by students was 16 with a percentage of 77% for the book's identity aspect, 80% for the authorship aspect, 85% for the book's strengths and 77% for the book's weaknesses. It can be concluded that using the mind mapping method in learning can improve students' understanding in writing reviews.